2017
DOI: 10.1186/s12934-017-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and catalytic properties of fungal extracellular cellobiose dehydrogenase produced in prokaryotic and eukaryotic expression systems

Abstract: BackgroundCellobiose dehydrogenase (CDH) is an extracellular enzyme produced by lignocellulolytic fungi. cdh gene expression is high in cellulose containing media, but relatively low CDH concentrations are found in the supernatant of fungal cultures due to strong binding to cellulose. Therefore, heterologous expression of CDH in Pichia pastoris was employed in the last 15 years, but the obtained enzymes were over glycosylated and had a reduced specific activity.ResultsWe compare the well-established CDH expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 46 publications
2
20
1
1
Order By: Relevance
“…This result is similar to the FAD occupancy published for T. reesei-produced CDH from C. thermophilus (CtCDH) [20]. In contrast, CtCDH expressed in P. pastoris contained only 30% FAD in the active site, whereas for native CtCDH 92% occupancy were reported [31].…”
Section: Spectroscopic Analysis (Uv/vis and Fad Loading)supporting
confidence: 87%
See 2 more Smart Citations
“…This result is similar to the FAD occupancy published for T. reesei-produced CDH from C. thermophilus (CtCDH) [20]. In contrast, CtCDH expressed in P. pastoris contained only 30% FAD in the active site, whereas for native CtCDH 92% occupancy were reported [31].…”
Section: Spectroscopic Analysis (Uv/vis and Fad Loading)supporting
confidence: 87%
“…In contrast, the prokaryotic expression host Escherichia coli would not introduce Oand N-glycans, but successful production of CDH has not been accomplished so far. Only expression of the sole dehydrogenase domain was achieved in E. coli [19,20]. Recombinant production of ascomycetous Corynascus thermophilus CDH in T. reesei and Aspergillus niger [20] indicated that fungal expression hosts could result in a lesser and more uniform glycosylation of recombinant CDH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the protein concentration of secreted CDH reported here (1489.30 mg L −1 ) is an improvement on previous attempts at methanol-induced expression, the volumetric activity and specific activity is lower than previously reported [21,[25][26][27]. Lowered specific activity has been observed in recombinant CDH production by P. pastoris due to a sub-stoichiometric occupation of catalytic sites within the flavin adenine dinucleotide (FAD) cofactor, as well as hyper-glycosylation [28]. Further, hyper-glycosylation may have affected the specific activity of both target enzymes, since the reported protein sizes ( Fig.…”
Section: Glycerol Fed-batch Fermentation Kinetics Yields and Productcontrasting
confidence: 61%
“…The reason can be minor differences in the FAD occupation of the active-site. 23 The observed differences of the IET between DH and CYT measured with the cytochrome c assay (1.27 to 1.98 U mg -1 ) vary to the same extent as the catalytic turnover and indicate that the introduced mutations exert no effect on the IET and CYT mobility.…”
Section: Recombinant Production Of Cdh Variantsmentioning
confidence: 93%